Analisis Penerimaan Model (Utaut) Terhadap Niat Penggunaan Mobile Bangking Mahasiswa FEB Unisma - Hikmatullah, Iksan; Wahono, Budi; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The aim of the research is to measure the intention to use mobile banking of FEB UNISMA students using the UTAUT model, which consists of four main constructs of performance expectations, business expectations, social influence and facility conditions. This research uses primary data sources through questionnaires. The sampling technique uses purposive sampling. The total sample was 85 FEB UNISMA student respondents class 2021-2024 with sample calculation using the Malhotra formula. This type of research is a quantitative approach with descriptive statistical analysis. The data analysis technique uses multiple linear regression with SPSS tools. The research results show that performance expectations, social influence, and facility conditions have a positive and significant influence on the intention to use mobile banking. Meanwhile, business expectations do not significantly influence the intention to use mobile banking for FEB UNISMA students class 2021-2024. Keywords: UTAUT, intention to use, mobile banking